Horticultural subsectors in St Lucia, St Vincent, Trinidad and Tobago and extra-regional markets of the Caribbean Common Market (Stevenson & Kellog Management Consultants TorontoCA, 1980)
Describes the horticultural subsector in St Lucia, St Vincent, and Trinidad and Tobago, and discusses extra-regional markets for the Caribbean Community. For each subsector describes the institutional environment within which the horticultural production, distribution and marketing systems operate. Also describes the production, marketing, handling and transporting, and processing of horticultural products.
Project report